O034 Autonomic control of heart rate stabilises with improvement of sleep disordered breathing in children with Down syndrome. (9th November 2022) - Walter, L; Varkey, J; Gu, C; Bassam, A; Davey, M; Nixon, G; Horne, R
Abstract: Background: Sleep disordered breathing (SDB) alters autonomic function, assessed using heart rate variability (HRV) in typically developing (TD) and children with Down syndrome (DS). SDB resolution in TD children normalises HRV, but the effects in children with DS are unknown. We compared HRV in children with DS with improved SDB (decrease in obstructive apnoea hypopnoea index (OAHI) to ≤ 50% of baseline OAHI) to those with unimproved SDB 2 y following baseline study. Methods: 24 children (3-19 y at baseline) were included. Power spectral analysis of the ECG determined low frequency (LF, parasympathetic and sympathetic activity), high frequency (HF, parasympathetic activity) power and LF/HF (sympathovagal balance). Children were grouped into Improved (n=12; 7 treated between studies) and Unimproved (n=12; 2 treated between studies). Results: OAHI decreased between studies in the Improved group (baseline, 29.5 (1.6, 154.0) [mean (min, max)] events/h; follow-up, 8.4 (0, 77.0); p<0.05), and worsened in the Unimproved group (baseline 6.1 (0, 22.9); follow-up 14.4 (0.3, 54.6); p<0.05). LF power was lower at follow-up in the Unimproved group compared to baseline during Total Sleep (p<0.05), N3 (p<0.05) and REM (p<0.01). HF power was also lower at follow-up in the Unimproved group during REM (p<0.05). HRV remained unchanged between baseline and follow-up for the Improved group. Conclusion: Autonomic control worsened as indicated by lower sympathetic and parasympathetic activity in children whose SDB was not improved. In contrast, in those children with improved SDB autonomic control remained the same, suggesting improvement in SDB severity prevents further worsening of autonomic control in children with DS.